Pengaruh loan to deposite ratio dan net interest margin terhadap return on asset - Agusri Agusri; Djoko Setyadi; Musdalifah Aziz (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aims to determine the effect of Loan to Deposite Ratio and Net Interest Margin to Return On Assets at regional development banks in Indonesia, using multiple regression analysis tools. The analysis tools used in this research are classical assumption test, multiple linear regression equation, correlation coefficient, coefficient of determination, F test (Simultan), and t test (partial). The value of the correlation coefficient (R) of 0.655, meaning that there is a strong relationship of variable Loan to Deposite Ratio and Net Interest Margin to ROA. The value of coefficient of determination (R2) of 42.9 percent this indicates the amount of contribution of variable loan to deposit ratio and net interest margin to rise and fall of ROA. From result of research by using partial test indicate that variable of loan to deposit ratio do not have significant effect to return on asset, while net interest margin variable have significant effect to return on asset. So from the two variables in the research only net interest margin variable that has a positive and significant effect on return on asset.Keywords: Liquidity, Net Interest Margin And Return On Asset